Dampak Pandemi Covid-19, Kurs dan Inflasi terhadap Pasar Modal Syariah: - Junaedi, Dedi; Safitri, Eka; Novita, Evi; Amalia, Rika Sri; Arsyad, Muhammad Rizal; Hermaliana, Mia (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The objectives of this study are: (1) To find out whether the Covid-19 pandemic, exchange rate and inflation have a partial effect on the movement of JII stock indexes. (2) To find out whether the Covid-19 pandemic, exchange rate and inflation have a partial effect on the movement of JII70 stock indexes. . (3) To find out whether the Covid-19 pandemic, exchange rate and inflation have a partial effect on the movement of ISSI stock indexes. As for the research conducted using quantitative methods. Data collection techniques are carried out by observation, documentation, literature study. Data analysis techniques use classical assumption tests including normality tests, multicolenearity tests, autocorrelation tests, heterochedasticity tests and hypothesis tests including partial tests (t tests), coefficient of determination (R) tests, F tests. . The results showed that simultaneously covid-19 cases, exchange rates, and inflation had a significant effect on the JII, JII70, and ISSI stock indices. . Partially, the exchange rate has a significant effect on the JII and JII70 stock indices are negatively correlated. Meanwhile, covid cases and inflation have an insignificant effect despite the trend. Meanwhile, partially covid cases, exchange rates and inflation have a significant effect on the ISSI Sharia stock index. Keywords : Covid-19 cases, exchange rates, inflation, and composite stock indices (JII, JII70, and ISSI)